KEMELIMPAHAN COCCINELLIDAE PADA PERTANAMAN JAGUNG YANG DIBERI KOMPOS GULMA SIAM (Chromolaena odorata) - Dewi Hastuti (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2011)
The objective of This research was to know indirect effect of siam weed compost to the population abundances of natural enemy Coccinellidae troughout corn plant performance. This research held on Banguntapan, Bantul, Yogyakarta from October 2009 until Marc 2010. It used Complete Randomized Design with 4 treatmens and 6 replications. The fertilizer treatmen consist of siam weed compost, cow menure compost, NPK, and control without fertilizer. Observation of Coccinellidae populatin had been done each 2 week. Result showed that the kind of fertilizer gived significantly effect of Coccinellidae population abundance. The highes Coccinellidae population given by siam weed compost treatmen (15), followed by cow menure compost (9), control (5) and the lowes one was NPK fertilizer (4).